ANALYSIS OF TOTAL OIL CONTENT IN THE MARINE WATERS OF DUMAI CITY - Hisbullah, Ali Akbar; Nedi, Syahril; Yoswaty, Dessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The Dumai City area is one of the regions currently designated as an industrial zone, a transportation route, and a busy international port. This situation puts significant pressure on the marine waters of Dumai City due to the waste produced. The primary source of marine pollution comes from oil spills, whether from ship operations, offshore drilling, or ship accidents. Pollution from oil spills in the ocean is a significant source of marine contamination that has consistently been a focus of public attention. This study aims to analyze the total oil content, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), and Total Organic Matter (TOM), as well as the effect of total oil content on DO, BOD, and TOM. The survey method used in this research involves collecting data from DO, BOD, TOM, and oil content measurements. The total oil content in Dumai City waters ranges from 0.14485 – 0.30214 ppm. The total oil content below the threshold still supports aquatic biota and does not damage the ecosystem. The DO content in Dumai waters ranges from 3.6 to 6.8 mg/L, and some measurements are below the threshold required to support marine biota. The BOD content of Dumai waters ranges from 10 to 11.3 mg/L, meaning that biological activity is still within optimal limits. The TOM content ranges from 17.38 – 35.22 mg/L, which does not support the life of aquatic biota, and there is potential for organic material pollution